Cak-Cok Greetings to the Community of Jatisrono Village North Surabaya City - Liyana Dian Prastiwi (Green Publisher Indonesia, 2022)
This is motivated by the phenomenon of the greeting form used by the people of Kampung Jatisrono who use the form of greeting cak-cok as a form of greeting that is used daily. This research itself aims to produce a description of what greeting words are used in the conversations of the people of Kampung Jatisrono and to produce a description of the impact caused by the community with the form of greeting used cak-cok. By using the ethnomethodology method which is carried out based on the fact that the participants in an interaction create a social order in the interaction situation, it is found that based on the form of greeting used by a person, in placing himself, it can be seen whether the person is trying to create social distance or actually building closeness/familiarity, sense of belonging. respect or even demeaning, insulting someone is implied by the form of greeting he uses.